2009
DOI: 10.1371/journal.ppat.1000682
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of CD244 and SAP Regulated CD8+ T Cell Responses of Patients with HTLV-I Associated Neurologic Disease

Abstract: HTLV-I-specific CD8+ T cells have been characterized with high frequencies in peripheral blood and cerebrospinal fluid and production of proinflammatory cytokines, which contribute to central nervous system inflammation in HTLV-I-associated myelopathy/tropical spastic paraparesis (HAM/TSP). However, little is known about the differences in CD8+ T cell activation status between asymptomatic carrier (ACs) and patients with HAM/TSP. The expression of CD244, a signaling lymphocyte activation molecule (SLAM) family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 70 publications
(98 reference statements)
0
26
0
Order By: Relevance
“…Although the inhibitory receptors PD-1 and Lag 3 do not appear to play a role in the selective loss of secondary effectors, our data implicate 2B4 as an immunomodulatory molecule that regulates memory cell expansion or survival during persistent antigen stimulation. Consistent with 2B4 mRNA and protein being up-regulated on exhausted CD8 + T cells during chronic LCMV, increased surface expression on virus-specific CD8 + T cells is found during human chronic diseases, such as HCV, HBV, HIV, HTLV-1 and melanomas (Bengsch et al, 2010; Casado et al, 2005; Enose-Akahata et al, 2009; Raziorrouh et al, 2010; Tarazona et al, 2002). The role of 2B4 on CD8 + T cell responses has not been well studied.…”
Section: Discussionmentioning
confidence: 55%
“…Although the inhibitory receptors PD-1 and Lag 3 do not appear to play a role in the selective loss of secondary effectors, our data implicate 2B4 as an immunomodulatory molecule that regulates memory cell expansion or survival during persistent antigen stimulation. Consistent with 2B4 mRNA and protein being up-regulated on exhausted CD8 + T cells during chronic LCMV, increased surface expression on virus-specific CD8 + T cells is found during human chronic diseases, such as HCV, HBV, HIV, HTLV-1 and melanomas (Bengsch et al, 2010; Casado et al, 2005; Enose-Akahata et al, 2009; Raziorrouh et al, 2010; Tarazona et al, 2002). The role of 2B4 on CD8 + T cell responses has not been well studied.…”
Section: Discussionmentioning
confidence: 55%
“…Various studies revealed, that exhausted CD8 + T cells exhibit increased 2B4 expression during chronic human diseases such as LCMV, HBV, HCV, HIV and also melanoma [100105]. Interestingly, the adaptor protein SAP contributes to a positive 2B4 signaling, which is higher expressed in effector T cells compared to exhausted T cells, whereas the exhausted ones display elevated 2B4 levels in chronic LCMV infection [100, 106].…”
Section: Inhibitory Receptors Associated With T Cell Exhaustionmentioning
confidence: 99%
“…Consistent with a role in exhaustion, in subjects chronically infected with hepatitis B virus, blockade of CD244 or CD48 resulted in enhancement of antiviral cytotoxicity and cytokine production (27). In contrast, for subjects with HTLV-I associated neurologic disease, blockade of CD244, or knockdown of the signaling molecule SAP, reduced HTLV-specific antiviral functions (28). In subjects with HIV infection, blockade of CD244 was found to enhance HIV-specific CD8 T cell proliferation from PBMC (22).…”
Section: Discussionmentioning
confidence: 99%